2012
DOI: 10.3174/ajnr.a3196
|View full text |Cite
|
Sign up to set email alerts
|

MR Spectroscopy of the Fetal Brain: Is It Possible without Sedation?

Abstract: BACKGROUND AND PURPOSE:The quality of spectroscopic studies may be limited because of unrestricted fetal movement. Sedation is recommended to avoid motion artefacts. However, sedation involves side effects. The aim of this study was to assess the feasibility and quality of brain 1 H-MR spectroscopy in unsedated fetuses and to evaluate whether quality is dependent on the type of spectra, fetal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…It can be technically challenging due to its susceptibility to motion artifacts, especially in the moving fetus, but its feasibility during fetal life has been widely shown [12,[51][52] . Our rate of valid spectra at short TE is similar to that reported by others at long TE in the BG on 1.5-tesla scanners [44,53] . Thus, Story et al [44] considered that 65% of the centrum semiovale spectra obtained from third-trimester fetuses was interpretable.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It can be technically challenging due to its susceptibility to motion artifacts, especially in the moving fetus, but its feasibility during fetal life has been widely shown [12,[51][52] . Our rate of valid spectra at short TE is similar to that reported by others at long TE in the BG on 1.5-tesla scanners [44,53] . Thus, Story et al [44] considered that 65% of the centrum semiovale spectra obtained from third-trimester fetuses was interpretable.…”
Section: Discussionsupporting
confidence: 77%
“…lipids) than short TE spectra, due to the faster relaxation of their protons compared to small metabolites. Accordingly, the success rates previously re- ported by Berger-Kulemann et al [53] in the BG region at 1.5 T and short TE were only 34%, compared to 66% at long TE. Although in the study by Story et al [45] the MRS selection criteria were not specified, the authors also used reference anatomic sequences before and after MRS in the same way we did, discarding data when there was evidence of fetal motion between the two [45,50] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lactate was observed in a small subset of our cohort. BergerKulemann et al 40 found lactate in 2 of their 6 normal fetuses (33.3%), whereas Story et al 30 described lactate in 3 healthy fetuses (7%) with normal deliveries and postnatal outcomes. The investigators postulate that lactate may be an important source of energy for the normally developing brain.…”
mentioning
confidence: 99%
“…Also, their long acquisition times (twice as long as our study) and their voxel placement in the centrum semiovale was different enough from ours to be able to make any meaningful comparisons. Most recently, Berger-Kulemann et al 40 retrospectively evaluated, with a 55% success rate, 1 H-MRS of 75 fetuses referred for MR imaging for suspected brain abnormalities. 41 It is important to note that, unlike other studies, our inception cohort only included low-risk healthy pregnant volunteers, which constituted a truly representative normative sample.…”
mentioning
confidence: 99%